PENINGKATAN HASIL BELAJAR IPA PESERTA DIDIK DENGAN MEDIA INTERAKTIF ANIMASI PADA MATERI PERKEMBANGAN MAKHLUK HIDUP - Muhammad Pallawagau, Andi; Irmawanty; Muafiah Nur, Andi (Jurnal Riset Guru Indonesia, 2024)
The primary issue addressed in this study is the lack of engaging and varied learning media used by teachers, leading to decreased student interest and focus, and consequently, low science learning outcomes. The objective of this research was to determine whether the implementation of interactive animated media as a teaching tool could enhance the science learning outcomes of fourth-grade students at UPTD SPF SDN 71 Maccini, Soppeng Regency. This classroom action research (CAR) study was conducted over two cycles, each comprising three meetings. The participants were 28 fourth-grade students at UPTD SPF SDN 71 Maccini, Soppeng Regency. Data collection methods included observation sheets, tests, and documentation. The results demonstrated an improvement in students' learning activities with the use of interactive animated media. In the first cycle, the average percentage of student learning activities was 70.36%, which increased to 91.07% in the second cycle. Additionally, the average science learning outcome score increased from 68.93 in the first cycle, where 19 students (32%) met the criteria for completion, to 88.68 in the second cycle, where 24 students (86%) met the criteria for completion. These findings suggest that the use of interactive animated media as a teaching tool can significantly enhance science learning outcomes and student engagement in learning activities. In conclusion, the application of interactive animated media as a learning medium effectively improves the science learning outcomes of fourth-grade students at UPTD SPF SDN 71 Maccini, Soppeng Regency, and enhances their overall learning activities.